Suppression Substractive Hybridization and NGS Reveal Differential Transcriptome Expression Profiles in Wayfaring Tree (Viburnum lantana L.) Treated with Ozone - Gottardini, Elena; Cristofori, Antonella; Pellegrini, Elisa; La Porta, Nicola; Nali, Cristina; Baldi, Paolo; Sablok, Gaurav (Frontiers in Plant Science, 2016)
Tropospheric ozone (O3) is a global air pollutant that causes high economical damages by decresing plant productivity. It entering leaves through the stomata, generating reactive oxygen species, which following decreases photosynthesis, plant growth, and biomass accumulation. In order to identify genes that are important for conferring O3 tolerance or sensitivity to plants, a suppression subtractive hybridization analysis was performed on the very sensitive woody shrub, Viburnum lantana, exposed to chronic O3 treatment (60 ppb, 5 h d-1 for 45 consecutive days). Transcript profiling and relative expression assessment were carried out in asymptomatic leaves, after 15 days of O3 exposure. At the end of the experiment symptoms were observed on all treated leaves and plants, with an injured leaf area per plant accounting for 4.2% of the total surface. Using 454-pyrosequencing, the transcriptome analysis of O3-responsive genes in leaves was performed, compiling a total of 38,800 and 12,495 high quality reads obtained in control and O3-treated libraries, respectively (average length of 319±156.7 and 255±107.4 bp). The Ensembl transcriptome yielded a total of 1241 unigenes with a total sequence length of 389,126 bp and an average length size of 389 bp (guanine-cytosine content = 49.9%). mRNA abundance was measured by reads per kilobase per million and 41 and 37 ensembl unigenes showed up- and down-regulation respectively. Photosynthetic performance of unigenes functionally associated to photosynthesis and carbon utilization was repressed, demonstrating the deleterious effect of O3 exposure. Unigenes functionally associated to heat-shock proteins and glutathione were concurrently induced, suggesting the role of thylakoid-localized proteins and antioxidant-detoxification pathways as an effective strategy for responding to O3. Gene Ontology analysis documented a differential expression of co-regulated transcripts for several functional categories, including specific transcription factors (MYB and WRKY). This study demonstrates that a complex sequence of events takes place in the cells at intracellular and membrane level following O3 exposure and elucidates the effects of this oxidative stress on the transcriptional machinery of the non-model plant species V. lantana, with the final aim to provide the molecular supportive knowledge for the use of this plant as O3-bioindicator.